2022
DOI: 10.1186/s12889-022-12802-z
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder dialogue on dilemmas at work as a workplace health promotion intervention including employees with a low SEP: a Responsive Evaluation

Abstract: Background The aim of this study was to evaluate the perceived changes of an innovative workplace health promotion intervention and evaluation. In this study, a bottom-up approach was taken to define the central themes and relevant outcomes of an intervention. These central themes and relevant outcomes of the intervention were defined together with stakeholders, including employees with a low socioeconomic position. Methods The intervention consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Moreover, we found that work/study time per week influenced burnout outcomes. Working too many hours may increase fatigue and decrease career satisfaction, which may increase job burnout risks [ 48 , 49 ]. Moderate working time helps dental postgraduates to complete their studies better and have adequate rest time to avoid exhaustion and reduce burnout risks.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that work/study time per week influenced burnout outcomes. Working too many hours may increase fatigue and decrease career satisfaction, which may increase job burnout risks [ 48 , 49 ]. Moderate working time helps dental postgraduates to complete their studies better and have adequate rest time to avoid exhaustion and reduce burnout risks.…”
Section: Discussionmentioning
confidence: 99%
“…26 31 32 In the responsive evaluation of the harbour service provider, changes were observed on four Open access levels: case, individual, team and organisational. 27 These changes included the implementation of a programme to enhance mutual understanding between departments, learning from one another and management's improved understanding of employees' issues.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout this commentary, examples are given from two recent WHP responsive evaluations performed over 2 years in two Dutch organisations with employees with low SEP: a harbour service provider (2018–2021) and a sheltered workplace (2019–2021). The evaluation papers have been/will be published elsewhere 27…”
Section: Introductionmentioning
confidence: 99%
“…In this learning process, understanding is gained on issues that are important for stakeholders, leading to changes in understanding, attitude, and sometimes organizational and/or individual behavior [52,110,170]. In the responsive evaluation of the harbor service provider, changes were observed on four levels: case, individual, team, and organizational [168]. These changes included the implementation of a program to enhance mutual understanding between departments, learning from one another, and management's improved understanding of employees' issues.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout this commentary, examples are given from two recent WHP responsive evaluations performed over two years in two Dutch organizations with employees with a low SEP: a harbor service provider (2018-2021) and a sheltered workplace (2019-2021). The evaluation papers have been/will be published elsewhere [168].…”
Section: Introductionmentioning
confidence: 99%